Pharmaceutical care in Brazilian community pharmacies: knowledge and practice - Reis, Tiago Marques dos (2015)
This study aimed to assess the pharmacist’s knowledge of the concept of pharmaceutical care and verify their practice in relation to this service. It involved a cross-sectional study carried out on community pharmacies in four Brazilian cities and involved pharmacists who work in community pharmacies. The pharmacists' knowledge of the concept of pharmaceutical care and their practice in respect of the service was measured. 486 pharmacies were visited and 112 pharmacists participated in the study. Of these professionals, 41% correctly identified the concept of pharmaceutical care and 70.5% said they perform it in pharmacies. The majority (n = 62) of the professionals followed standard operating procedures and four recorded data on the service offered (patient information, interventions and results). There is evidence that only 2.5% of the professionals effectively carry out the level of pharmaceutical care recommended by the Brazilian guidelines. Pharmacists are not yet ready to perform pharmaceutical care in community pharmacies. It is necessary to review the pharmacists’ training and enable the professionals to properly perform this service.